Changes in Health Information Exchange Use Behavior After Introduction of a Fast Healthcare Interoperability Resources (FHIR) Application - Kampman, Haleigh M; Rivera, Rebecca L; Park, Seho; Schaffer, Jason T; Hancock, Amy; Rahurkar, Saurabh; Musey, Paul; Kuhn, Diane; Vest, Joshua R; Schleyer, Titus K (AMIA ... Annual Symposium proceedings, 2024)
The aim of our study was to characterize emergency department clinicians' health information exchange (HIE) use patterns after the implementation of a Fast Healthcare Interoperability Resources (FHIR) application. Using longitudinal electronic health record log data, we categorized HIE use behavior as: no HIE use (0), Web-based viewer use only (1), FHIR application use only (2), or Web-based viewer and FHIR application use (3). We sequenced HIE use behavior from September 2019 to February 2023, then employed hierarchical agglomerative clustering to identify clinician characteristics associated with each HIE use pattern. Our results showed four usage patterns representing (1) clinicians who "lagged" in HIE use and continued as sporadic HIE users (n=66, 46.1%), (2) "late adopters" who had more consistent usage over time (n=32, 22.4%), (3) "legacy users" whose preferred modality was the Web-based viewer (n=25, 17.5%), and (4) "mixed modality users" who displayed frequent changes in HIE access modality (n=20, 14.0%).